Students' Learning Motivation in Online Learning in View of Self-Concept and Family Support - Hakim, Siti Nurina; Rasyida, Nuril Arga (Urecol Journal. Part A: Education and Training, 2023)
The use of online media is one of the solutions so that teaching and learning activities between teachers and students can continue, even though in the implementation of online media problems often occur. The decision to switch to online learning media will affect conducive interactions between teachers and students, if the method used is not appropriate it will make students less interested and bored, the impact is that students become lazy, passive and less interested in learning. The purpose of this research is to find out student's learning motivation in online learning in terms of self-concept and family support. The research hypotheses are: (1) student motivation in online learning has a relationship with self-concept and family support, (2) there is a positive relationship between learning motivation and self-concept, (3) there is a positive relationship between learning motivation and family support. This study uses a correlational quantitative method. The population of the study is SMP 1 Muhammadiyah Surakarta. A sample of 100 students was determined by purposive sampling. The data collection tool uses the Learning Motivation Scale, the Self-Concept Scale, and the Family Support Scale. Data analysis technique using multiple linear regression. The results of multiple regression analysis yield (F) = 134,999 with a sig.p value <0.01, (r) = 0.847 (>0), with a Sig. (1-tailed) p <0.01, and value (r) = 0.652 (r>0), with a value of Sig. (1-tailed) p < 0.01. This shows that there is a very significant positive relationship between self-concept and family support and learning motivation, shows a very significant positive relationship between self-concept and learning motivation, and shows a very significant positive relationship between family support and learning motivation.